(untitled) (Dissertare, 2019)
Since ancient times, humanity has celebrated the change of the seasons with allegorical festivities and, in particular, the summer solstices, June 21 and winter, on December 21. The festival of Saint John the Baptist coincides with the first of them. This contribution shows a poorly studied vision of the festivals of this saint in Venezuela, where there is a perception that everything is already said about it, which limits the treatment of the subject to the repetition of consecrated common places. This documentary work focuses on the festivals of San Juan Bautista in Carora, a colonial city of the semi-arid of the Venezuelan western, traditional and deeply religious, trying to approach an answer about the absence of drum ringing at the saint’s festivities in that city, which celebrates with a very sober religious and social holiday, unlike the coast and other places in the country. The analysis presented is part of the current of the School of the Annals, framed in religious mentalities and from social history. This contribution contributes to the study of the complexity of the celebrations of San Juan in Venezuela, describing their variants in the country, then showing the dominance of the Catholic Church over the slave population, through the brotherhoods and the control of the farms, as the main element that explains the absence of the African influence in the festivities in honor of the patron saint in the levitical city of Carora.